Barriers Barriers to Physical Activity Programs in Patients with Type 2 Diabetes Mellitus (T2DM) in Yogyakarta: A Qualitative study - Kusumo, Mahendro Prasetyo; Kusumawati, Wiwik (Unnes Journal of Public Health, 2022)
The difficulty of the community to understand health behavior is the main cause of poor physical activity behavior. The aim of this study is to explore health education barriers to controlling blood glucose patient with DM in primry health care. The Forum Group Discussion (n = 22) and interview (n = 5) methods were to explore the patient's desire to overcome educational barriers. Informants were patients with DM aged of 26-69 year-old from two community health center and two private health center in Sleman Regency, Indonesia. The questions were around barriers to physical activity programs for controlling blood glucose. The data were analyzed using Opencode. Boring educational training is the leading cause of physical activity and dietary control in patients with DM. Formal language in delivering material is the cause of patient boredom to take part in the training. Despise and feeling of anxiety to ask questions during the educational procedure that the patient feels. Also, in terms of health service providers, limited human resources have resulted in a lack of maximum education programs for patients with DM in Yogyakarta.Tense atmosphere and language that is difficult to understand have a negative impact on patient behavior to change physical activity behavior and controlled eating patterns in patients with DM.